2020
DOI: 10.3390/ijms21010333
|View full text |Cite
|
Sign up to set email alerts
|

Gluconacetobacter diazotrophicus Changes The Molecular Mechanisms of Root Development in Oryza sativa L. Growing Under Water Stress

Abstract: Background: Inoculation with Gluconacetobacter diazotrophicus has shown to influence root development in red rice plants, and more recently, the induced systemic tolerance (IST) response to drought was also demonstrated. The goal of this study was to evaluate the inoculation effect of G. diazotrophicus strain Pal5 on the amelioration of drought stress and root development in red rice (Oryza sativa L.). Methods: The experimental treatments consist of red rice plants inoculated with and without strain Pal5 in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…IWD is one of the major problems facing crop productions (including maize), especially in dry (arid and semi-arid) regions, which limits crop productivity. Improving IWD tolerance in maize through ecofriendly sustainable strategies is the key to securing foods for the growing human population [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…IWD is one of the major problems facing crop productions (including maize), especially in dry (arid and semi-arid) regions, which limits crop productivity. Improving IWD tolerance in maize through ecofriendly sustainable strategies is the key to securing foods for the growing human population [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The production of plant TSS as well as its involvement in drought stress management is well documented in soybean [ 61 ], wheat [ 62 ], and rice [ 61 ]. Our study also found similar results, reporting a net increase in TSS in camelina and canola upon exogenous application of Se (foliar as well as seed priming).…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro EPS production observed in all strains could be related with bacterial protection and plant colonization during drought stress; according to [ 44 ] the accumulation of EPS protected the cells of Gluconoacetobacter diazotrophicus against oxidative stress under in-vitro conditions and during the colonization of rice plants. Moreover, roots secrete organic compounds used by the bacteria for phytohormone biosynthesis; these compounds promote plant-cell division rate in roots and shoots, and, hence, increasing biomass gains and nutrient uptake [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%